Transmural Ultrasonography in the Evaluation of Horse Hoof Internal Structures: Comparative Qualitative Findings—Part 1 (2023)
ABSTRACT: Ultrasonography is commonly used to evaluate equine lameness-related structures, but traditional hoof approaches cannot adequately visualize internal structures such as the lamellar layer. To address this limitation, we used 62 healthy hooves without digital radiographic abnormalities, made up of thirty anatomical pieces (phase 1) and thirty-two hooves from living horses (phase 2). In both phases, half of the digits were submerged in water (group 1) and the other half in water and ice (group 2) for 24 h. Ultrasonographic views and temperature and humidity measurements were taken every two hours, and sagittal sections were obtained in phase 1. Good quality images were obtained in both phases. The transmural technique allowed the evaluation of several structures of the DEJ (tubular and lamellar strata of the hoof wall, sublamellar dermis, and solar and coronary papillae) and of the distal phalanx (extensor process, parietal surface, and apex). Our findings suggest that the transmural technique following hoof submersion can be useful for internal evaluation of hoof conditions, such as laminitis. However, further validation of the technique in natural or experimental cases is required.